Pengaruh Implementasi Green Banking, Corporate Social Responsibility terhadap Nilai Perusahaan pada Perusahaan Perbankan yang terdaftar di BEI - Romli Romli; Ali Rahman Reza Zaputra (Portofolio: Jurnal Ekonomi, Bisnis, Manajemen, dan Akuntansi, 2021)
This study aims to examine the effect of green banking implementation, disclosure of corporate social responsibility on firm value in banking companies listed on the IDX. In this study, implementation of green banking is measured by the presence or absence of policies on provision of environmentally sound lending, disclosure of corporate social responsibility is measured by the number of disclosures of company public information is divided by indicators based on GRI-G4, and company value is measured by the Tobin's Q model. The population in this study is banking companies listed on the Indonesia Stock Exchange in 2017–2019. The research sample data was determined based on the purposive sampling method, to obtain a sample of 109 samples consisting of 36 companies for 2017 and 2018 and 37 companies for 2019. Data analysis techniques used multiple linear regression analysis with firm value as the dependent variable, and green banking implementation, disclosure of corporate social responsibility as an independent variable. Based on the test results, it was found that the green banking implementation variable had a negative effect on firm value. Meanwhile, the variable of Corporate Social Responsibility disclosure has no effect on firm value.